Optimization of turbo-expander operating parameters to enhance Liquids (LPG and Condensate) recovery. - Guerch Mohammed Islam; Ahmed abdelmouiz (Amar Telidji University – Laghouat Faculty of Technology Department of Process Engineering, 2025)
Among the most important facilities dedicated to gas processing are the Joule-Thomson valve and the expansion turbine, commonly known as the Turbo-expander. These are essential devices used to reduce the pressure of raw gas, a necessary step for separating heavier hydrocarbons. To achieve low pressure and temperature at the outlet, the proper functioning of the expander must be ensured. The study of the variation of the Turbo Expander's operating parameters enabled us to determine the optimal parameters for improving liquids recovery, especially considering that no changes to the equipment sizing will be necessary. After optimization, a gain of 19.23 tons/day of LPG and 12.216 tons/day of condensate was achieved.
Specialty: Gas Engineering